Are Men Given Priority for Top Jobs? Investigating the Glass Ceiling in the Italian Academia - Maria De Paola; Michela Ponzo; Vincenzo Scoppa (Institute for the Study of Labor (IZA), 2016)
We aim to investigate if men receive preferential treatment in promotions using the Italian system for the access to associate and full professor positions that is organized in two stages: first, candidates participate in a national wide competition to obtain the National Scientific Qualification (NSQ), then successful candidates compete to obtain a position in University Departments opening a vacancy. We investigate the probability of success in the two stages in relation to the candidate's gender, controlling for several measures of productivity and a number of individual, field and university characteristics. Whereas no gender differences emerge in the probability of obtaining the NSQ, females have a lower probability of promotion at the Department level. Gender gaps tend to be larger when the number of available positions shrink, consistent with a sort of social norm establishing that men are given priority over women when the number of positions is limited.
Keywords: J71; M51; J45; J16; D72; D78; 330; gender discrimination; glass ceiling; academic promotions; natural experiment